On a Fourier problem for evolution differential-functional equations with nonlocal boundary conditions - Bokalo, M.; Dmytriv, V. (Нелинейные граничные задачи, 2003)
The boundary value problems with nonlocal boundary conditions have been treated in many works. Individually, Day [1] while studying quasistatic thermoelasticity posed a model involving parabolic equation with nonlocal boundary condition. This model has been expanded into more general problems [1,2]. The results of these papers concern the boundary value problems with an initial condition. In the current paper, we consider Fourier Problem (the problem without initial conditions) for evolution differential-functional equations with nonlocal boundary conditions.